Representasi Moralitas Dalam Iklan Teh Botol Sosro Versi “Semeja Bersaudara” - Aji Sulistyo (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
Television advertisement is an effective medium that aims to market a product or service, because it combines audio and visuals. therefore television advertisement can effectively influence the audience to buy the product or service. Advertisement nowadays does not only convey promotional messages, but can also be a medium for delivering social messages. That is one form of the function of the media, which is to educate the public. The research entitled Representation of Morality in the Teh Botol Sosro Advertisement "Semeja Bersaudara" version analyzed the morality value in a television advertisement from ready-to-drink tea producers, Teh Botol Sosro entitled "Semeja Bersaudara" which began airing in early 2019. In this study researchers used Charles Sanders Peirce's Semiotics theory with triangular meaning analysis tools in the form of Signs, Objects and Interpretations. In addition, researchers also use representation theory from Stuart Hall in interpreting messages in advertisements. The results of this study found that the "Semeja Bersaudara" version of Teh Botol Sosro advertisement represented a message in the form of morality. There are nine values of morality that can be taken in this advertisement including, friendly attitude, sharing, empathy, help, not prejudice, no discrimination, harmony, tolerance between religious communities and cross-cultural tolerance. The message conveyed in this advertisement is how the general public can understand how every human action in social life has moral values, so that the public can understand and apply moral values in order to live a better life.